Model of cw argon ion lasers excited by low-energy electron beams - Fetzer, G. J., author; Collins, G. J., author; Rocca, Jorge J., author; Jacobs, R., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1986)
A model of cw argon ion lasers excited by low-energy (50-200 eV) direct current electron beams at current densities between 1 and 50 A/cm2 has been developed. The electron energy distribution in the electron-beam-created plasma is calculated by numerically solving the Boltzmann equation for electrons. Optical gains, powers, and laser efficiencies were computed for the 4765-, 4880-, 4965-, and 4658-Å Ar II transitions for a wide range of discharge conditions. Laser efficiencies comparable to those of a conventional Ar II laser (~3 × 10-4) are predicted for these laser transitions when electron beam excitation is used.